Acidic decomposition of scheelite by organic sodium phytate at atmospheric pressure. (1st October 2021) - Liu, Xuheng; Xiong, Jiajin; Chen, Xingyu; Li, Jiangtao; He, Lihua; Sun, Fenglong; Zhao, Zhongwei
Graphical abstract: Highlights: A green and natural organic phytate was used as decomposing reagent for scheelite. The formation process of phosphotungstate by complexation of W and P was investigated. The decomposition rate of scheelite can reach 99.18% with only 2 g/L organic phosphorus. Abstract: The alkali residue formed during the alkaline decomposition of scheelite produces serious environmental pollution. A new acidic decomposition method for scheelite using sulfur-phosphorus mixed acid process has been industrialized, but it requires a high concentration of phosphoric acid. In this paper, sodium phytate, a green and natural organic phytic acid salt, was used as a chelating agent to decompose scheelite under acidic conditions. In the leaching process, calcium was precipitated by H2 SO4 to generate insoluble CaSO4 in the residue, while tungsten was chelated by sodium phytate to form stable macromolecular multinuclear organic chelates in the solution. A satisfactory tungsten leaching extent of 99.39% was achieved using 10 g/L sodium phytate, 1 mol/L H2 SO4, and a liquid/solid ratio of 8:1 at 353 K for 3.5 h. As such, the phosphorus consumption was significantly reduced in the sodium phytate leaching system without high temperature and pressure. This innovative process provides a new method for extracting tungsten from scheelite, which reduces the consumption of phosphorus and is environmentally friendly.